2014
DOI: 10.1186/1746-1596-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Trichomonous vaginalis by microscopy, latex agglutination, diamond’s media, and PCR in symptomatic women, Khartoum, Sudan

Abstract: BackgroundTrichomoniasis is the most common sexually transmitted disease. However, limited data are available on an effective technique for the diagnosis of Trichomonas vaginalis.MethodsA cross-sectional study was conducted to evaluate the accuracy of wet mount microscopy, latex agglutination, Diamond’s media, and polymerase chain reaction (PCR) for detection of T. vaginalis among symptomatic women who attended the gynecological clinic at Khartoum, Sudan.ResultsOf the 297 women studied, 252 (84.8%) were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…A metaanalysis including 24 studies had been performed by Zhang and Begg and it was concluded that a significant association existed [30]. Isolation rates of Trichomonas vaginalis is influenced strongly by socio-demographic parameters of the study groups like residence, religion, age, sex; population recruited that is STD clinic attendees or women undergoing routine screening in community, clinical presentation defined by presence or absence of symptoms and laboratory methodology used [53,54].…”
Section: B Prevalence Of General Population and In Patients With Ca mentioning
confidence: 99%
“…A metaanalysis including 24 studies had been performed by Zhang and Begg and it was concluded that a significant association existed [30]. Isolation rates of Trichomonas vaginalis is influenced strongly by socio-demographic parameters of the study groups like residence, religion, age, sex; population recruited that is STD clinic attendees or women undergoing routine screening in community, clinical presentation defined by presence or absence of symptoms and laboratory methodology used [53,54].…”
Section: B Prevalence Of General Population and In Patients With Ca mentioning
confidence: 99%
“…As known before, trichomoniasis prevalence in pregnant women is influenced by demographic characteristics, 22 the participants' sexual behavior, 23 and the diagnostic method used. 13 In this study, almost all participants were low risk pregnant women to have trichomoniasis based on demographic characteristics and sexual behaviour. However, the study participant with a positive test result of Trichomonas rapid test was a woman with trichomoniasis risks: in active sexual age (24 years old), had low level of education (junior high school graduated), had early coitarche (at 18 years old), and had multiple sexual partners throughout her life (three partners).…”
Section: Resultsmentioning
confidence: 91%
“…23 In addition, the diagnostic method used may also affect the prevalence of trichomoniasis. 13 Some of the demographic factors significantly associated with trichomoniasis occurrence in pregnant women include active sexual age, 22,24 low levels of education, 22 as well as occupation as a prostitute. 16 High rates of trichomoniasis in the active sexual population are associated with higher sexual activity, lack awareness of STIs, as well as changes in vaginal microbiota (especially during menstrual periods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One advantage inherent to T. vaginalis culture is cultivation of viable organisms for nitroimidazole susceptibility testing,11 particularly in patients who experience treatment failure.The performance of a second non-molecular adjunct to microscopy, T. vaginalis antigen detection, is also dependent on geographic prevalence. In the cohort with approximately 85% T. vaginalis prevalence, 99.6% sensitivity of the Kalon TV latex agglutination test (Kalon Biological, Surrey, UK) was reported compared to PCR 3. Abu-Sarkodie et al47 documented a kappa index of 0.93 for result agreement between this latex agglutination assay and InPouch TV; molecular diagnostics were not incorporated into the study.…”
mentioning
confidence: 99%